EKSTRAKSI OLEORESIN JAHE (Zingiber officinale) KAJIAN DARI UKURAN BAHAN, PELARUT, WAKTU DAN SUHU - Anam, Choirul (MAPETA, 2010)
This study aimed at investigating the best condition in terms of material size, solvent type, time and temperature of the extraction process to produce oleoresin. This study consisted of two stages. This study used the Block Randomized Design with six replications. Experiment I was a single factorial experiment consisting of three treatments, the material size of 20 mesh, 40 mesh and 60 mesh. The best result yielded in the first experiment was used for the second experiment. Experiment II consisted of three factors, the treatment of which were arranged in a nested design. Each treatment was repeated three times. Factor I, the solvent, consisted of two levels: ethanol and acetone. Factor II, the time, consisted of three levels: one hour, three hours and five hours. Factor III, the tempetarature, consisted of three levels : (30±1)oC, (40±1)oC and (50±1) oC.Experiment I revealed that the best result was yielded at a material size of 40 mesh, an oleoresin content of 20.60 % and a volatile oil concentration of 21.26 %. Experiment II showed that the usage of ethanol solvent for three hours at a temperature of 40oC yielded the best ginger oleoresin. The extract contained 22.12 % oleoresin, 20.27 % volatile oil content, and 9.20 % solvent remains with a 1.5173 deviation index.The conclusion of this study is that the best ginger oleoresin axtract is produced from a material size of 40mesh using the extraction condition of ethanol solvent for 3 hours at 40oC.Key words : ginger, oleoresin, extract